EFFECT OF OPERATING PARAMETERS OF HYDRAULIC FRACTURING TECHNOLOGY AND RESERVOIR POROSITY ON FRACTURE GEOMETRY - Truong, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2017)
In the past decades, a large amount of oil production in the Cuu Long Basin was mainly exploited from the basement reservoir and one part from oil production in the Miocene sandstone reservoir, and a small amount of oil production from the sandstone Oligocene reservoir. Many discovery wells and production wells in lower Oligocene sandstone had high potential of oil and gas production reserves in which the average reservoir porosity was from 10% to 18%, and reservoir permeability was in the range of 0.1 md to 5 md.  Due to high reservoir heterogeneity, complicated geological structure in high closure pressure up to 7,700 psi, the problem in the Oligocene reservoir is very poor fracture conductivity among the fractures with the upper seal and lower seal by shale. The big challenging deal with this problem is to stimulate the reservoir by hydraulic fracturing to enhance oil and gas production which is required to the study. In this article, the author has presented the effects of operating parameters of hydraulic fracturing as injection time, injection rate, leak-off coefficient, and reservoir porosity based on the 2D PKN-C fracture geometry accounting for leak-off coefficient, spurt loss in terms of power law parameters on economic performance by design of experiment (DOE) and apply a tool of response surface method with the recommended ranges of operating parameter in the field experience. In the recent years, through the successful application of hydraulic fracturing to stimulate reservoirs for well completion in Oligocene reservoir, that technique has widely been used in the field for improving oil production